Power Network of Penghulu Adat in The Concurrent Regional Election in West Sumatera - Asrinaldi Asrinaldi (Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
This article describes the power network of Minangkabau’s penghulu adat in West Sumatera. As known in West Sumatera, the penghulu has a strategic position in the Minangkabau community. Its position in traditional institutions is of utmost importance, especially in bridging the interests of the community in the political and governance processes in the nagari. This is deemed feasible as penghulu adat is capable of optimizing their power network and utilizing traditional institutions that they congregate in. In explaining the power network of penghulu, this study used a descriptive type of qualitative approach.  Furthermore, this research found various types of formation in penghulu’s power network which serves as the basis for their involvement in the political process of the village. Firstly, the establishment of penghulu power networking through personal capabilities recognized by the community in the village. Secondly, the establishment of penghulu power networking through traditional authority. Thirdly, the establishment of penghulu power networking which originates from the additional legitimacy of local governments, particularly for penghulu considered to represent the local government’s interests in the village. Fourthly, the establishment of penghulu power networking based on the recognition of their peers by bestowing the title of sangsako in the tribe.